Does pleasure facilitate healthy drinking? The role of epicurean pleasure in the regulation of wine consumption - Petit, O; Wang, QJ; Spence, CJ (Wiley, 2022)
Research on food psychology demonstrates that epicurean eating tendencies (i.e., esthetic appreciation of the sensory and symbolic value of food), similar to health concerns, tend to be associated with more regulated eating behaviors. Given that wine is already a product that is more pleasure-oriented, the question to be addressed here is whether such epicurean tendencies exert a similar effect in terms of moderating wine consumption. Two online studies demonstrate that, contrary to this suggestion, people with epicurean drinking tendencies in fact report drinking wine more frequently, and in larger quantities, than those with health beliefs. That said, when such pleasure is explicitly emphasized through textual cues, it appears to promote more regulated wine consumption. Impaired control mediates the effects of drinking tendencies as well as the effects of cueing on wine consumption. These results highlight how stressing epicurean pleasure might prove to be an effective strategy for those marketers and public authorities wanting to promote responsible wine consumption. Success in this regard might depend on whether it is the perception of the product that is cued rather than the consumers' self-perceived wine consumption.